2014
DOI: 10.1515/pterid-2014-0007
|View full text |Cite
|
Sign up to set email alerts
|

Fetal hydrocephalus

Abstract: The aim of this study was to draw the attention of specialists faced with fetal hydrocephalus in the postnatal period to the possibilities of prenatal diagnosis and further monitoring by studying isolated and syndrome cases in fetuses. One hundred and nine fetuses from a total of 2238 autopsies were the subject of observation in this study. In 64 (58.7%) of the studied fetuses, isolated hydrocephalus was found, while the other 45 cases were associated with the following malformations: Arnold-Chiari type II, Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The role of consanguinity is also known for the occurrence of congenital malformations such as hydrocephalus, postaxial polydactyly of the hands, and defects of the lips and palate [13,14]. Almost all studies have documented a slightly higher percentage of male fetuses in cases of CH in live births and stillbirths as well as in fetopathologic autopsies [15][16][17][18]. Van Landingham et al did not find a difference in the genders of the children with hydrocephalus compared to the general population [4].…”
Section: Discussionmentioning
confidence: 99%
“…The role of consanguinity is also known for the occurrence of congenital malformations such as hydrocephalus, postaxial polydactyly of the hands, and defects of the lips and palate [13,14]. Almost all studies have documented a slightly higher percentage of male fetuses in cases of CH in live births and stillbirths as well as in fetopathologic autopsies [15][16][17][18]. Van Landingham et al did not find a difference in the genders of the children with hydrocephalus compared to the general population [4].…”
Section: Discussionmentioning
confidence: 99%
“…The surfactant therapy was promoted in the 80s and became the standard treatment for children with RDS or at RDS risk. It has been confirmed that surfactant therapy reduced extra-alveolar gas collection, neonatal mortality rate and mortality rate in suckling age as well as costs for treatment of the surviving infants 17 , 18 . Natural surfactants extracted from animal sources containing surfactant proteins (SP-B) and (SP-C), as well as synthetic surfactants with functional protein analogues of SP-A and SP-C have been comprehensively studied in preterm newborns with or at risk of RDS.…”
Section: Introductionmentioning
confidence: 90%